Economic Survey of Latin America and the Caribbean 2018 - United Nations (United Nations, 2018)
The 2018 edition of the Economic Survey of Latin America and the Caribbean, its seventieth issue, consists of three parts. Part I outlines the region’s economic performance in 2017 and analyses trends in the early months of 2018, as well as the outlook for the rest of the year. It examines the external and domestic factors that have influenced the region’s economic performance, analyses the characteristics of economic growth, prices and the labour market, and draws attention to some of the macroeconomic policy challenges of the prevailing external conditions, amid mounting uncertainty stemming mainly from political factors. Part II of this edition, which has three chapters, analyses the dynamics of investment and its determinants, with a view to identifying the different variables on which public policy can act to influence the trajectory of investment. Part III contains notes relating to the economic performance of the countries of Latin America and the Caribbean in 2017 and the first half of 2018, together with their respective statistical annexes.